Investigation of the factors that influence employees' participation in development activities. - Noe, Raymond A.; Wilk, Steffanie L. (Journal of Applied Psychology, 1993)
In a field study, the factors that influence employees' participation in development activities are investigated. The proposed model hypothesized that the influence of self-efficacy and work environment perceptions on development activity is mediated by learning attitudes, perceptions of development needs, and perceived benefits. Attitudinal and perceptional data and self-report and objective measures of development activity were collected from employees in health maintenance (N = 343), financial services (N = 196), and public sector engineering firms (N = 496). No statistical support was found for the proposed mediated relation. However, motivation to learn, perception of benefits, and work environment perceptions had significant unique effects on development activity